The Impact of Value Co-Creation Behaviour within the Social Media Context - Sleilati, Esther Bassil; Sfeir, Cynthia Jabbour (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study investigates the impact of value co-creation behaviour on customer loyalty within the context of social media. It also attempts to determine the role played by customer brand experience and customer satisfaction as mediating variables. Design/Methodology/Approach: Drawing upon the service-dominant logic theory, a research framework is developed and tested using the structural equation modelling. The data comprise the input of 449 respondents from Lebanon. Research findings: The findings provide substantial evidence showing the relationship between customer value co-creation behaviour and customer loyalty. This relationship is partially mediated by customer brand experience. Theoretical contribution/Originality: This study expands on existing literature by investigating how customer value co-creation behaviours can lead to customer loyalty within the social media context of Lebanon. Practitioner/Policy implications: The findings can assist managers in understanding how customer loyalty can be promoted through co-creation behaviours within social media. The results suggest that managers should provide the means which can encourage more behavioural, intellectual and affective customer reviews/feedback. Research limitation/Implications: The limitation of this study rests on its findings which cannot be generalised to a wider business community as it focuses only on the context of Lebanon. Keywords: Online Customer Brand Experience, Online Customer Loyalty, Online Customer Satisfaction, Online Customer Value Co-Creation Behaviour, Service-Dominant Logic, Social Media JEL Classification: M31